Adding eptinezumab to brief patient education to treat chronic migraine and medication-overuse headache: Protocol for RESOLUTION—A phase 4, multinational, randomized, double-blind, placebo-controlled study - Jensen, Rigmor H.; Schytz, Henrik Winther; Tassorelli, Cristina; Terwindt, Gisela M.; Carlsen, Louise N.; Mittoux, Aurélia; Østerberg, Ole; Lipton, Richard B.; Tepper, Stewart J.; Blumenfeld, Andrew; Lundqvist, Christofer (Frontiers in Neurology, 2023)
Introduction: Migraine is a highly prevalent and disabling neurological disease. Excessive use of 28 acute medications can lead to medication-overuse headache (MOH), occurring when a patient 29 experiences an increasing number of headache and migraine days, despite taking greater amounts of 30 acute medication. To treat MOH, a preventive migraine treatment and/or withdrawal of the overused 31 medication(s) are advised. Brief Educational Intervention (BEI) has been shown to be an effective 32 tool with promising results for MOH. Here, we report the design of a clinical trial that aims to 33 evaluate the efficacy of eptinezumab, an anti-calcitonin gene-related peptide preventive migraine 34 treatment, as an add-on to BEI for treatment of MOH in those with chronic migraine. 35 Methods and analysis: RESOLUTION will be a phase 4, multi-national, randomised, double-blind, 36 placebo-controlled study. This study will enroll approximately 570 participants with dual diagnoses of 37 chronic migraine and MOH. Eligible patients will be randomly allocated to one of two treatment 38 groups, BEI and eptinezumab (100 mg; n=285) or BEI and placebo (n=285), in a 1:1 ratio. The 39 primary endpoint is the change from baseline in monthly migraine days over weeks 1–4. Secondary 40 and exploratory endpoints will assess monthly migraine days over weeks 1–12, MOH remission, 41 transition from chronic to episodic migraine, health-related quality of life, work productivity, and the 42 safety and tolerability of eptinezumab in this patient population. 43 Ethics and dissemination: This study will be conducted in accordance with good clinical practice. 44 All patients will be fully informed about the study, including the risks and benefits of participation, 45 and all participants will provide informed consent for participation in the trial and dissemination of 46 results. 47 Trial registration: The trial registration number is NCT05452239. The results of this study will be 48 disseminated through peer-reviewed journals, conference presentations, and social media.